A study on complementary feeding practices among mothers in urban and rural areas - Javalkar, Sandhya Rani; Aras, Radha Y. (International Journal Of Community Medicine And Public Health, 2018)
Background: Adequate nutrition during infancy and early childhood is essential to ensure the growth, health, and development of children to their full potential. Complementary feeding is a process starting when breast milk alone is no longer sufficient to meet the nutritional requirements of infants, and therefore other foods and liquids are needed, along with breast milk. The objective was to study complementary feeding practices and the various factors influencing them in urban and rural areas. Methods: A community based cross sectional study was conducted in Urban and Rural area of Mangalore Taluk. Data was collected by interview method among 408 mothers using a predesigned pretested questionnaire, information regarding demographic profile, socio-economic status, complementary feeding practices, etc was collected. Results: As many as 186 (45.3%) i.e., 129/186 (69.3%) mothers in the rural area and 57/186 (30.6%) mothers in urban area started complementary feeds at the age of 6 months. The most common food preferred as complementary food was combination of rice and dal together. The number of meals per day given to the child varied from 2-4/day. The number of snacks given per day to the child varied from 1-4 /day; commonly preferred snacks were Biscuits both in urban and rural areas Bottle feeding was practiced by 181 (44.4%) of the mothers, that included 113/181 (62.4%) from rural area and 68/181 (37.5%) from urban area. Conclusions: Poor complementary feeding practices were observed both in rural and urban areas. Family member’s advice, poor knowledge and influence of baby food marketing strategies have resulted in inappropriate practices.